2014
DOI: 10.1016/j.aogh.2014.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Burden in Latin America and the Caribbean

Abstract: Establishing knowledge on the real impact of incidence, mortality, and survival in Latin America and the Caribbean is quite a challenge due to the lack of an updated and dynamic information system on mortality and incidence, although some improvement has been made in the information systems of some countries within the most recent decade. Other obstacles for cancer control are the uneven allocation of resources, lack of investments in equipment and infrastructure, and the concentration of health care professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 25 publications
2
14
0
5
Order By: Relevance
“…Nonetheless, more efforts are required. The highest incidence and mortality rates found in these countries agree with previous studies [5,8,43], which showed that in Cuban and Brazilian men both OC incidence and mortality tend to increase.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Nonetheless, more efforts are required. The highest incidence and mortality rates found in these countries agree with previous studies [5,8,43], which showed that in Cuban and Brazilian men both OC incidence and mortality tend to increase.…”
Section: Resultssupporting
confidence: 91%
“…It is the fifth most frequent cancer among men in Brazil [6]; whereas men in Cuba present a higher mortality for this type of cancer in comparison with their peers in the United States and Canada, with a tendency to increase [7]. This reflects a clear disparity between sexes, where men bear 72% of the burden of this disease in the region, with standardized mortality ratios from OC (8.7) being surpassed only by lung cancer (11.0) [8]. However, more relevance and social intervention have been given to other types of cancer that are less prevalent and in other population groups.…”
Section: Introductionmentioning
confidence: 99%
“…Across the Caribbean, few epidemiologic studies are available on cervical cancer incidence and survival [14]. Over the last decade, the burden of cervical cancer has been established and several National Cancer Plans have been presented.…”
Section: Discussionmentioning
confidence: 99%
“…Decades of Papanicolaou-based screening to detect pre-cancerous cervical lesions in a few countries of the region have not had a major impact in reducing CC incidence and mortality rates, which are still high across LA. Moreover, estimates indicate an overall 72% increase in the incidence of CC and a 78% rise in mortality by this disease between 2012 and 2030 (6). Each year, about 1.1 million new CC cases and 600,000 deaths are recognized in LA and the Caribbean.…”
Section: Epidemiology Of Hpv-related Neoplasias In Lamentioning
confidence: 99%